Urban land markets and urban land development. An examination of three Brazilian cities: Brasília, Curitiba and Recife - Mozart Vitor Serra; David E. Dowall; Diana Meirelles da Motta; Michael Donovan (Institute for Applied Economic Research (ipea), 2015)
This paper synthesizes and extends the results of urban land market studies carried out in three Brazilian cities - Brasília, Curitiba and Recife. The purpose of the studies is to empirically assess the performance of urban land markets in different cities and to gauge the feasibility of applying the Land Market Assessment methodology in Brazil. The project involved the collaboration of several organizations: The World Bank, Instituto de Pesquisa Econômica Aplicada (IPEA), Secretaria de Estado de Desenvolvimento Urbano e Habitaç\~ao (SEDUH), Instituto de Pesquisa e Planejamento Urbano de Curitiba (IPPUC), and Fundaç\~ao de Desenvolvimento Municipal (FIDEM). The field research was carried out in 2003.
Keywords: J11; R21; R31; R38; 330